1992
DOI: 10.1007/bf00027153
|View full text |Cite
|
Sign up to set email alerts
|

An mRNA that specifically accumulates in maize roots delineates a novel subset of developing cortical cells

Abstract: A near full-length cDNA clone (pZRP3) corresponding to an mRNA that accumulates specifically in roots of maize was isolated. The ZRP3 mRNA is ca. 600 nucleotides in length. The amino acid sequence of the predicted polypeptide is rich in leucine (16%), proline (11%), and cysteine (8.5%). The zrp3 gene appears to be expressed exclusively in roots, whereas other ZRP3-related genes are expressed in additional organs of the maize plant. In situ hybridization shows that ZRP3 mRNA accumulation is largely confined to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
80
0

Year Published

1995
1995
2001
2001

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(84 citation statements)
references
References 38 publications
4
80
0
Order By: Relevance
“…In situ hybridization to RNA using paraffin-embedded sections was conducted as described previously (John et al, 1992;Ke et al, 1997). 35S-Labeled RNA probes (sense and antisense) were synthesized from a subclone consisting of the 3'-most 600 nucleotides of the CAC2 cDNA.…”
Section: In Situ Techniquesmentioning
confidence: 99%
“…In situ hybridization to RNA using paraffin-embedded sections was conducted as described previously (John et al, 1992;Ke et al, 1997). 35S-Labeled RNA probes (sense and antisense) were synthesized from a subclone consisting of the 3'-most 600 nucleotides of the CAC2 cDNA.…”
Section: In Situ Techniquesmentioning
confidence: 99%
“…Northern blot analysis suggests that an mRNA encoding a caffeic acid 0-methyltransferase (COMT) involved in lignin biosynthesis accumulates preferentially in com roots (Collazo et al, 1992). An mRNA (ZRP3) in com that encodes a protein whose function is unknown accumulates largely in the cortical ground meristem of the root (John et al, 1992). A homolog (AX92) from Brassica napus accumulated in a similar fashion (Dietrich et al, 1989), and another homolog (DC2.15) in carrot was expressed during somatic embryogenesis (Aleith and Richter, 1990).…”
Section: Root-preferential Gene Expressionmentioning
confidence: 99%
“…To begin the investigation of the molecular mechanisms of root development and function, we isolated three cDNA clones that corresponded to mRNAs that accumulated preferentially in the roots of maize (John, 1991;John et al, 1992). This report documents the characterization of one of these cDNA clones, and an analysis of the transcriptional control for another.…”
Section: Root-preferential Gene Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…LEDI-2 cDNA, whose expression was specifically observed in the dark, was cloned from cell cultures by a subtractive hybridization technique . The deduced polypeptide sequence shares a significant homology to the known plant proteins specifically expressed in the root, such as ZRP3, RCc2, PVR5 (John et al, 1992, Xu et al, 1995, Choi et al, 1996, but the biological roles of those polypeptides have so far been unknown. Northern blot hybridization and recent functional analyses of LEDI-2 indicated that the gene product of LEDI-2 has a close correlation with the production of shikonin in the cell cultures .…”
Section: Ledi-2 Expression In Shoot Stemmentioning
confidence: 99%